Analysis, Opportunities, Threats, and Strategies for Indonesia’s International Trade in Squid with China in 2025 - Gita Mei Wulandari (CV SCRIPTA INTELEKTUAL MANDIRI, 2026)
This study examines the opportunities, threats, and strategic prospects of Indonesia's squid exports to China in 2025 through a non empirical qualitative approach grounded in international trade theory and strategic analysis. The research employs a conceptual and descriptive design based on the systematic review of scholarly literature, official government reports, and international trade databases. The analysis reveals that Indonesia possesses significant export opportunities derived from abundant marine resources, growing Chinese seafood demand, favorable bilateral economic relations, and expanding integration within regional trade networks. The study also identifies several external challenges, including increasing competition from Vietnam, Thailand, and India, stringent quality and food safety requirements, certification barriers, logistical inefficiencies, seasonal production fluctuations, maritime security concerns, and geopolitical uncertainty affecting international trade. Strategic evaluation indicates that strengthening product quality, improving certification compliance, modernizing cold chain systems, enhancing logistics performance, expanding market intelligence capabilities, promoting digital trade, encouraging product diversification, fostering stakeholder collaboration, and supporting sustainable resource management are essential for maintaining long term competitiveness. The findings contribute to international trade and fisheries export literature by providing an integrated framework for understanding Indonesia's competitive position in the Chinese squid market and identifying strategic priorities for sustainable export development.